2017
DOI: 10.1186/s13104-017-2645-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inhaled corticosteroids use and associated factors among asthmatic patients attending Tikur Anbessa Specialized Hospital, Ethiopia

Abstract: BackgroundInhaled corticosteroids (ICSs) are cornerstone therapy for persistent asthma. However, underutilization of ICSs is common and little is known about factors contributing toward this undesirable use.MethodsA cross-sectional study was conducted through interview and chart review among persistent asthmatic patients attending chest clinic of Tikur Anbessa Specialized Hospital from 1 May to 31 September 2014. A total of 131 eligible patients who attended the clinic during study period were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Among the included studies the prevalence of nonadherence to inhaled medications varied from 15.1% reported by Ayele et al [23] to 59% reported by Koyra and Table 1 Characteristics of studies included in the systematic review and meta-analysis of the non-adherence to inhaled medications among asthmatic patients in Ethiopia, 2020 Chinasho [22]. To look at the heterogeneity of the included studies, we conducted subgroup analysis by regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies the prevalence of nonadherence to inhaled medications varied from 15.1% reported by Ayele et al [23] to 59% reported by Koyra and Table 1 Characteristics of studies included in the systematic review and meta-analysis of the non-adherence to inhaled medications among asthmatic patients in Ethiopia, 2020 Chinasho [22]. To look at the heterogeneity of the included studies, we conducted subgroup analysis by regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been published on the prevalence and associated factors of non-adherence to inhaled medications among adult asthmatic patients in Ethiopia [18][19][20][21][22][23], the general prevalence remains unknown. Therefore, the primary purpose of this systematic review and meta-analysis is to determine the pooled national prevalence of non-adherence to inhaled medications among adult asthmatic patients in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Each item is scored using a 1-5 scale and then summed up (total score, . The score was then classified as well controlled (20)(21)(22)(23)(24)(25), not well controlled (16)(17)(18)(19), and very poorly controlled (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) asthma. For the purpose of data analysis, the total score was dichotomized.…”
Section: Asthma Control Test (Act) Andmentioning
confidence: 99%
“…Moreover, for people in older age groups, premature death due to asthma contributes more to the burden of disease [4]. Unavailability of appropriate and affordable medications, poor knowledge of patients, and poor communication between physician and patient increased the burden of asthma in Ethiopia [5].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these deaths can be avoided through timely and appropriate treatment. Medications used in asthma are classi ed as relievers and controller [3]. These are corticosteroids and leukotriene modi ers and bronchodilators.…”
Section: Introductionmentioning
confidence: 99%